Cynthia Ozick's comic art - Cohen, Sarah Blacher (Indiana Univ. Press, 1994)
Bringing to bear insights from Jewish, literary, and cultural studies, Sarah Blacher Cohen sheds new light on the works of one of America's foremost writers. Arguing persuasively that Ozick's fiction is a form of comedy, Cohen interweaves religion and literature, skillfully illuminating the complex relationship between the comic and the sacred. Where others have emphasized Ozick's intellectualism and Jewish learning, Cohen foregrounds whimsicality, grotesque realism, irony, satire, and exuberance as the defining characteristics of Ozick's art in such works as Trust, The Cannibal Galaxy, The Messiah of Stockholm,
Keywords: Ozick; Cynthia; Geschichte; Comic; The; in literature; Jewish women; Jews in literature; Judaism in literature; Women and literature; Literatur; Komik; Juden